Tinjauan Hukum Tindakan Administratif Keimigrasian Terhadap Warga Negara Asing Di Indonesia Dengan Undang-Undang Nomor 6 Tahun 2011 Tentang Keimigrasian - Thariq Megatama; Elwidarifa Marwenny (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
Globalization has led to an increase in interaction between countries, which in turn has led to an increase in the flow of people leaving and entering a country. According to Minister of Law and Human Rights Regulation No. 44 of 2015, increased international mobility requires stricter supervision of foreigners entering Indonesian territory. Immigration has an important role in regulating and supervising foreigners entering a country in accordance with Law Number 6 Year 2011 on Immigration. Article 2 of the law states that the supervision of foreigners aims to protect national interests. The limitations of the problems in this paper are 1) Policies implemented by Indonesia against foreigners entering the Indonesian Territory; 2) The system of supervision of foreigners that has been implemented by the Indonesian government; and 3) Application of Immigration Administrative Measures against foreigners in the Indonesian Territory. The method used is normative law by analyzing primary legal materials such as Law No. 6 of 2011, as well as secondary legal materials so that conclusions are obtained; 1) The entry of foreigners into Indonesia must be in accordance with selective policies, which include entry, stay, and exit from the territory of Indonesia 2) Immigration conducts surveillance to reduce the possibility of misuse of applicable laws and regulations and take action against foreigners who violate the rules in order to maintain the immigration function. 3) Immigration acts as a law enforcer, and guardian of the development of supervision to reduce the possibility of abuse of applicable laws and regulations and take action against foreigners who violate the rules in order to maintain the immigration function.